REVIEW ON THE RCCS FUNCTION TO ANTICIPATE THE STATION BLACK-OUT ACCIDENT IN RGTT200K - Piping Supriatna; Sriyono Sriyono (Badan Tenaga Nuklir Nasional, 2015)
RGTT200K is a conceptual design reactor based on HTGR technology, implementing active, passive and inherent safety system. The reactor safety systems are designed in “defence in depth” philosophy. RGTT200K has a reactor cavity cooling system (RCCS) which is designed to remove the heat from the reactor vessel to the structure of the containment. The RCCS is designed to fulfill this role by preserving the reactor vessel under the maximum allowable tempera-ture during normal operation and protecting the reactor containment structure in the event of failure of all active cooling systems. The performance and reliability of the RCCS, therefore, are considered as critical factors in determining maximum design power level after heat removal. This paper dis-cusses the review of RCCS function during the station blackout (SBO) accident. During SBO, all of active cooling systems are failed to work and the heat removal is conducted by the RCCS. The SBO is an event in which there is no electricity from diesel generator to the blower. The methodology used is based on paper review concerning the RCCS function and experiences in Germany, USA, Japan, and China. RCCS in RGTT200K has two equipments, first is active mode and second is passive mode equipment. Based on that review, the RCCS is capable to maintain the RPV temperature below 65ºC at normal operation and 125ºC during the SBO. The RCCS keep the fuel of below 1600°C and maintain its integrity to avoid radioactivity release to the environment.